FACTORS FOR PROMOTING THE DEVELOPMENT OF HIGH-TECH INDUSTRIES OF THE NATIONAL ECONOMY OF UKRAINE - MYTSENKO, Valerii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In the study, attention is updated to the issues of formation and implementation of an effective state policy of ensuring the stimulation of the development of high-tech industries as a leading factor in strengthening the competitiveness of the national economy.The purpose of the study is to identify the factors stimulating the development of high-tech industries in the national economy of Ukraine.It is argued that the state of development of high-tech industries in Ukraine at the pre-war stage of the functioning and development of its economy was not high, and in the conditions of a full-scale war and a critically difficult business environment, post-war recovery takes on an even more pessimistic scenario. The shortcomings and problematic aspects of activation of innovative and technological activity in Ukraine are pointed out. Using the method of correlation-regression multivariate analysis based on the data of the EU-27 countries regarding the numerical values of the sub-indices of the Global Innovation Index, the Global Talent Competitiveness Index and the World Digital Competitiveness Index, the factors influencing innovative technological development and economic growth were identified.The key directions and areas of destabilization of the development of high-tech industries, as well as the tools for managing the innovative and technological activities of enterprises in Ukraine in the conditions of war and post-war recovery, have been determined. A list of institutional and organizational measures implemented in the regions of Ukraine aimed at stimulating the development of innovative technological activities and high-tech industries is provided. Factors stimulating the development of the high-tech industry sector in Ukraine have been identified.
Keywords: high-tech sector; industry 4.0; innovative and technological activity; factors and means of stimulation; national economy